AFIKSASI ISTILAH PERTUKANGAN (KAJIAN SINGKAT ASPEK MORFOLOGIS BAHASA BALI) - I Made Suweta; I Made Susila Putra; Putu Wuladari Tristananda (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2023)
The Balinese language is included in a large regional language group that has an effective oral and written tradition as an intra-tribal Balinese spoken language. The term carpentry is one of the terms contained in the Balinese language. There are several Balinese language carpentry terms which can be distinguished in two ways, namely the Balinese language carpentry terms in basic and affixed forms. Balinese carpentry terms are in basic forms (nouns, verbs, monosyllables, disyllabic and trisyllabic). Balinese carpentry terms have affixes (N-, ma-, ka-, and a-), suffixes (-a, -ang, -in, -an, -n, -e, and -ne), and confixes (ma -an and pa-an).  Keywords: Balinese carpentry terms, basic forms, and affixes